2022
DOI: 10.1007/s13659-022-00323-6
|View full text |Cite
|
Sign up to set email alerts
|

The bibenzyl derivatives of Dendrobium officinale prevent UV-B irradiation induced photoaging via SIRT3

Abstract: Dendrobium officinale is a valuable medicinal herb that is widely used in traditional Chinese medicine. The chemical constituents of D. officinale have attracted much attention and a large number of compounds have been reported including many bibenzyl derivatives. 13 bibenzyl derivatives from D. officinale were sent for molecular docking, surface plasmon resonance (SPR) assay and after detection of Mn-SOD and SIRT3 activities in or not in HaCaT cells, it was concluded that bibenzyl derivatives did not directly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…54) It has been reported that, bibenzyl derivatives as the main composition of D. officinale can protect cells from UVB irradiation induced photoaging by activating Sirtuin-3 (SIRT-3) activity. 55) According to these research results, the anti-photoaging mechanism of D. officinale is not very clear, and most reports show that active components in D. officinale can play a role in a certain metabolic pathway. Therefore, different from other manuscripts, in which the anti-photoaging effect of DOP-1 generated after fermentation of D. officinale was characterized, we extracted all the active components after fermentation of D. officinale and comprehensively analyzed its anti-photoaging effect.…”
Section: Discussionmentioning
confidence: 99%
“…54) It has been reported that, bibenzyl derivatives as the main composition of D. officinale can protect cells from UVB irradiation induced photoaging by activating Sirtuin-3 (SIRT-3) activity. 55) According to these research results, the anti-photoaging mechanism of D. officinale is not very clear, and most reports show that active components in D. officinale can play a role in a certain metabolic pathway. Therefore, different from other manuscripts, in which the anti-photoaging effect of DOP-1 generated after fermentation of D. officinale was characterized, we extracted all the active components after fermentation of D. officinale and comprehensively analyzed its anti-photoaging effect.…”
Section: Discussionmentioning
confidence: 99%
“…The GLUT-1 protein solution was fixed on the surface of the Series S CM5 Sensor chip (GE Healthcare) with binding and deionization times of 120 and 150 s, respectively, and then the CSGs solution (25, 50, 100, 200, 400 µg/mL) passed through the sensor surface at a speed of 30 µL/min. The Kinetics and affinity analyses of CSCs at different concentrations were calculated by Biacore S200 evaluation software (GE Healthcare) [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…1,2 In Vietnam, D. officinale has been found in the mountains and forests of Vinh Phu, Quang Tri, Quang Nam, Da Nang, Gia Lai, Lam Dong provinces. The previous studies reported terpenoids, 3 bibenzyl derivatives, [1][2][3][4][5][6][7] polysaccharides, [8][9][10][11][12][13][14][15] are the main components of this plants. Some of which exhibited antitumor, 7,14,15 anti-inammatory activities [8][9][10][11][12][13] and alleviates type 2 diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…9 Therefore, the whole plants of D. officinale were selected for further study. This paper reported the isolation, structural identication of thirteen triterpene glycosides (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13), including seven undescribed compounds (1)(2)(3)(4)(5)(6)(7) and their anti a-glucosidase and a-amylase activities in vitro.…”
Section: Introductionmentioning
confidence: 99%